G4P2A1 Hamil 38 Minggu Belum Inpartu dengan HAP e.c Plasenta Akreta dengan Riwayat SC Satu Kali, Janin Tunggal Hidup, Letak Lintang : Sebuah Laporan Kasus - Fukrapti Fukrapti; Restu Krisnanda; Nurul Islamy (Medula, 2022)
Placenta accreta is the abnormal implantation of the placenta in the uterine wall. The risk factors for placenta accreta include a history of myometrial damage due to cesarean section, placenta previa, maternal age > 35 years, and multipara. Meanwhile, the transverse lie is when the position of the fetus is perpendicular to the mother. The predisposition factors for transverse fetal position are multipara, placenta previa, and uterine myoma. Mrs. YS, G4P2A1, 32 years old, was referred from Way Kanan Hospital with bleeding from the genitals 3 weeks before she entered to the hospital. The bleeding was fresh red, no pain, 3 times changing pads per day. The patient was diagnosed with placenta accreta at 6 months of gestation. Examination of vital sign, general physical examination, and complete haematological examination were within normal limits. Obstetrical physical examination revealed fundal height of 3 fingers bellow the Xyphoideus Processus with estimated fetal weight of 2.790 gram, and transverse lie. Ultrasound results showed the impression of a single live fetus in a transverse position, biparietal diemeter indicated 38 weeks 3 days of gestational age with the placenta closing the OUI, pathological lacunae, hypervascularization, and bridging vessels. The patient underwent laparotomy and total hysterectomy. Postoperatively, ceftriaxone 1 gram/12 hours IV therapy, tranexamic acid 500 mg/8 hours IV, ketorolac 30 mg/8 hours, and transfusions of 2 PRC and 2 WB kolf were given. Post-transfusion haemoglobin 10.8 g/dL.